2022
DOI: 10.1007/s40747-022-00767-w
|View full text |Cite|
|
Sign up to set email alerts
|

A survey on COVID-19 impact in the healthcare domain: worldwide market implementation, applications, security and privacy issues, challenges and future prospects

Abstract: Extensive research has been conducted on healthcare technology and service advancements during the last decade. The Internet of Medical Things (IoMT) has demonstrated the ability to connect various medical apparatus, sensors, and healthcare specialists to ensure the best medical treatment in a distant location. Patient safety has improved, healthcare prices have decreased dramatically, healthcare services have become more approachable, and the operational efficiency of the healthcare industry has increased. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 139 publications
0
15
0
Order By: Relevance
“…However, if CAIDA is used, large data set cannot be stored in the system thus high case external attacks is not prevented. In [19][20][21][22][23], data detection in industrial applications is analysed as data in entire segment inside the industry must be protected in reaching external users. Thus, the protection is provided using machine learning algorithm with two directional data flow procedures.…”
Section: Research Gap and Motivationmentioning
confidence: 99%
“…However, if CAIDA is used, large data set cannot be stored in the system thus high case external attacks is not prevented. In [19][20][21][22][23], data detection in industrial applications is analysed as data in entire segment inside the industry must be protected in reaching external users. Thus, the protection is provided using machine learning algorithm with two directional data flow procedures.…”
Section: Research Gap and Motivationmentioning
confidence: 99%
“…There are many researchers who have provided good overviews in the arena of IoMT. Shamsoshoara et al [ 18 ] provided security measures using PUF; Fernández-Caramés et al [ 19 ] showed the challenges of security measures; Alwarafy et al [ 20 ] presented intrusion detection using edge computing; Shakeel et al [ 21 ] showed security systems in limited scale; Al-Garadi et al [ 22 ], Arora et al [ 23 ], and Rbah et al [ 24 ] presented deep-learning based intrusion detection system; and only blockchain-based measures are presented by Sengupta et al [ 17 ], Sawadi et al [ 25 ], and Khor et al [ 26 ]. This paper presents not only the issues and challenges of IoMT application that are highlighted, but security and privacy risks with both centralized and decentralized solutions are presented.…”
Section: Contributionsmentioning
confidence: 99%
“…Segmentation is achieved by operating as parameters with some functions. This approach provides good accuracy, robust quality, and accuracy [ 39 ].…”
Section: Related Workmentioning
confidence: 99%